Fish consumption rate, fish processing method and stunting prevelance in Kuta Blang Village, Samadua Sub-District, South Aceh - Asrari, Suharni; Husna, Arfah; Khairi, Ikhsanul (Acta Aquatica: Aquatic Sciences Journal, 2022)
Stunting is the nutritional status based on the index of PB/U or TB/U where in anthropometric standards of research on the nutritional status of children, the measurement results are in the Threshold of (z-scrore) <-2 SD to -3 SD (short/stunted). Indonesian has a fairly high prevelance of Stunting. One of the causes is inadequate nutrition during the growth period. Rating fish can provide protein and micronutrient nutrition to supportchildern's growth and development. The purpose of this study was to determine the relationship between fish consumption Rates, processing methods and Stunting prevalence. This research is a type of case control study. With research subjects 117 families (78 non-stunted families and 39 stunted families). The research was conducted in the village of Kuta Blang, Samadua district, South Aceh district in September-October. Statistical analysisi using Chi-square test. From this study, it was found that there was no relationship between the number of fish consumption (p=309) and theprvalence of Stunting and there was a significant relationship between how to process (cook) fish and the prevelance of Stunting (p=0,002).Keywords: fish consumption; how to process; stuntingKeywords: fish consumption; how to process; stunting